2007
DOI: 10.1152/ajpheart.01017.2006
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac neural crest ablation inhibits compaction and electrical function of conduction system bundles

Abstract: Retroviral and transgenic lineage-tracing studies have shown that neural crest cells associate with the developing bundles of the ventricular conduction system. Whereas this migration of cells does not provide progenitors for the myocardial cells of the conduction system, the question of whether neural crest affects the differentiation and/or function of cardiac specialized tissues continues to be of interest. Using optical mapping of voltage-sensitive dye, we determined that ventricles from chick embryos in w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
60
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(63 citation statements)
references
References 52 publications
2
60
0
Order By: Relevance
“…6,31,32 In parallel, inductive signals from the NCC have been proposed to regulate the development and maturation of the central conduction system. 33,34 Our Cx40-Cre lineage study suggests that VCS lineage restriction occurs by E16.5 in both ventricles, indicating that temporal as well as spatial regulation of inductive signals may be involved in the transition to lineage restriction and the control of VCS outgrowth. Indeed, previous work has revealed a late role for Nkx2.5 in maturation of Purkinje fiber network.…”
Section: Miquerol Et Almentioning
confidence: 87%
“…6,31,32 In parallel, inductive signals from the NCC have been proposed to regulate the development and maturation of the central conduction system. 33,34 Our Cx40-Cre lineage study suggests that VCS lineage restriction occurs by E16.5 in both ventricles, indicating that temporal as well as spatial regulation of inductive signals may be involved in the transition to lineage restriction and the control of VCS outgrowth. Indeed, previous work has revealed a late role for Nkx2.5 in maturation of Purkinje fiber network.…”
Section: Miquerol Et Almentioning
confidence: 87%
“…However, a number of recent studies using transgenic mice with NCC specific cre recombinase activity have shown that NCC not only migrate within the cells of the conduction system lineage but that they play a significant role in their final maturation [38,40,41]. Gurjarpadhye et al [34] have also observed abnormal conductivity in hearts of chick embryos after the ablation of their cardiac NCC. Thus, consistent with the above, we postulate that Zn deficiency could affect either the development of the conduction system directly or the ability of NCC to participate in CCS maturation and innervation; either effect would result in impaired heart formation.…”
Section: Discussionmentioning
confidence: 99%
“…NCC are essential to support normal heart morphogenesis [28][29][30][31] and alterations in the population, the developmental migration, or metabolism of NCC by surgical ablation, genetic deletion, or teratogenic insults lead to a panoply of cardiovascular defects [32][33][34][35][36][37][38]. Cardiac NCC originate from the lateral ridges of the neuroectoderm that span between the mid-otic placode and the caudal end of the third somite and contribute ectomesenchymal cells towards the development of the pharyngeal arches, the carotid, subclavian, innominate and coronary arteries, the aorticopulmonary septum, the conotruncal cushions, the distal portion of the ventricular septum, the walls of the ascending aorta, and the pulmonary trunk [28,29,39] and participate in the maturation of the cardiac conduction system [29,38,40,41].…”
Section: Introductionmentioning
confidence: 99%
“…Ablation of CNC in chicken results in defects of the atrioventricular bundle, Purkinje fiber, and OFT. 134,135,137,138 OFT misalignment and persistent truncus arteriosus, abnormal patterning of the great arteries, and abnormal myocardial function are part of these defects. Thus, congenital defects in the OFT or the great vessels mediated by CNC may affect cardiac electrophysiology indirectly.…”
Section: Cardiac Neural Crest Cellsmentioning
confidence: 99%